Pengaruh Faktor Sanitasi terhadap Kejadian Pedikulosis Kapitis di Panti Asuhan Kota Palembang - Nova Tria; Chairil Anwar; Rico Januar Sitorus (Jurnal Epidemiologi Kesehatan Komunitas, 2019)
Background: Pedikulosis capitis is the most common ectoparasitosis in the whole world. This disease is endemic globally in developed and developing countries that have tropical and subtropical climates head lice are obligate blood-sucking which has the potential to cause anemia. Itching caused by flea saliva can cause children to have difficulty sleeping, disrupt the concentration of learning, resulting in a decrease in achievement at school. The spread of pediculosis is supported by the fact that this disease is more often diagnosed in children from dysfunctional families, orphanages and special schools that live in dormitories. This study aims were to analyze the correlation between sanitation factor to the incident of pediculosis capitis.Methods: An analitycal observational study was conducted with a cross sectional design on January 2019. There were 382 samples that had  inclusion dan exclusion criteria. Data collected from anamnesis questionnaires and hair examinations of respondents. The result were analyzed using chi-square and logistic regression.Result: 160 respondents (41,9%) had been found positif pediculosis capitis. Statistical test showed that humidity factor had significant association to the incident of pediculosis capitis (p=0.000) and OR= 2.210.Conclusion : Children who lived in rooms with range of humidity 70-90% had 2 times the chance to suffer pediculosis capitis compared to children who lived in outside the range